Associations between resistance training motivation, behaviour and strength. Issue 3 (4th May 2022) - Murray, Ross M.; Howe, Holly S.; Sylvester, Benjamin D.; Willson, Erin; Sabiston, Catherine M.
ABSTRACT: Resistance training is an important component of exercise that has widespread positive distinct health benefits. However, studies examining exercise motivation typically assess general forms of exercise, thus unable to identify motivational distinctions between aerobic and resistance training. Three studies were conducted to explore the distinction between exercise modalities and to examine the extent to which behavioural regulations for resistance training relate to behaviour and strength outcomes. In Study 1 participants (N = 148) completed questionnaires assessing which exercise modalities were considered by the word "exercise". In Study 2 participants (N = 216) completed questionnaires assessing aerobic and resistance training motivation and behaviour. In Study 3 participants (N = 100) completed measures of resistance training motivation and behaviour, as well as upper and lower body strength tests. In Study 1, we observed bias in participants understanding of the term "exercise", whereby exercise is conflated with aerobic training. In Study 2, compared to general exercise motivation, resistance training motivation was more strongly correlated with resistance training behaviour. Finally, Study 3 demonstrated that more self-determined regulations for resistance training were positively correlated to resistance training behaviour and objective assessments of physical strength. Consistent with the tenets of Self-determination theory, intrinsic motivation for resistance training was the strongest predictor of physical strength outcomes. Overall, results indicate the efficacy in specifying resistance training motivation when developing research and/or exercise interventions targeting motivational influences.